2017
DOI: 10.1123/pes.2016-0176
|View full text |Cite
|
Sign up to set email alerts
|

Beta-Alanine Supplementation Improves Throwing Velocities in Repeated Sprint Ability and 200-m Swimming Performance in Young Water Polo Players

Abstract: The purpose of this study was to investigate the effects of beta-alanine supplementation on specific tests for water polo. Fifteen young water polo players (16 ± 2 years) underwent a 200-m swimming performance, repeated-sprint ability test (RSA) with free throw (shooting), and 30-s maximal tethered eggbeater kicks. Participants were randomly allocated into two groups (placebo × beta-alanine) and supplemented with 6.4g∙dayof beta-alanine or a placebo for six weeks. The mean and total RSA times, the magnitude ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 0 publications
2
10
2
Order By: Relevance
“…At these sample sizes, the Type I error rate for the "possible" threshold is 22% to 45% and for the "likely" threshold is 12% to 22% (Fig 3A and 3B). Consistent with these calculations, we noticed numerous studies in which effects associated with large p-values (for H o =0)-often in the 0.2 to 0.3 range-were declared "likely" or higher by MBI [36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52]. See Fig 4 for "Although parametric analysis was unable to demonstrate significant differences, magnitude-based inferences indicated that the change in 1-RM squat showed a likely benefit from PA on increasing lower body strength and a very likely benefit for increasing lean body mass (LBM)."…”
Section: Resultssupporting
confidence: 79%
“…At these sample sizes, the Type I error rate for the "possible" threshold is 22% to 45% and for the "likely" threshold is 12% to 22% (Fig 3A and 3B). Consistent with these calculations, we noticed numerous studies in which effects associated with large p-values (for H o =0)-often in the 0.2 to 0.3 range-were declared "likely" or higher by MBI [36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52]. See Fig 4 for "Although parametric analysis was unable to demonstrate significant differences, magnitude-based inferences indicated that the change in 1-RM squat showed a likely benefit from PA on increasing lower body strength and a very likely benefit for increasing lean body mass (LBM)."…”
Section: Resultssupporting
confidence: 79%
“…At these sample sizes, the Type I error rate for the "possible" threshold is 22% to 45% and for the "likely" threshold is 12% to 22% (Fig 3A and 3B). Consistent with these calculations, we noticed numerous studies in which effects associated with large p-values (for H o = 0)-often in the 0.2 to 0.3 range-were declared "likely" or higher by MBI [36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52]. See Fig 4 for an example from the literature.…”
Section: Plos Onesupporting
confidence: 76%
“…Due to the importance of repeated efforts in water polo, nutritional strategies to improve repeated effort ability have been a focus of some studies [ 6 8 ], especially ergogenic aids that could improve the buffering capacity [ 6 8 ], since repeated efforts can promote increases in muscular acidosis [ 9 ], which is considered an important factor to promote fatigue [ 10 ]. Initially, sodium bicarbonate supplementation was investigated [ 6 ], however no beneficial effects were found, while more recently, some studies investigated the effects of β-alanine supplementation [ 7 , 8 ], showing a small but substantial beneficial effect on performance [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Carnosine (β-alanyl-L-histidine) has multiple functions [e.g., antioxidant [ 14 ], anti-glycation of proteins [ 15 ], and muscle contractility regulation [ 16 ], of which the main function is as an intracellular acid buffer [ 12 ] due to a pKa of 6.83 [ 17 ]. Thus, 4 weeks of β-alanine supplementation is enough to improve muscle buffering capacity by ~4% [ 11 , 12 ], which promotes high accumulations of ions H + in muscle [ 10 ], and consequently improves high-intensity efforts that last between 1 and 4 min [ 10 , 18 ], such as repeated sprints in water polo [ 7 , 8 ] and total work done at 110% in cycling [ 12 ], among others.…”
Section: Introductionmentioning
confidence: 99%